What is the True Cost of AI Drug Discovery? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The development of a new pharmaceutical drug has long been characterized by a staggering investment of time and capital. The traditional process can span 10 ...
Keywords: Drug Discovery; Digital Health; Artificial Intelligence; Healthcare Innovation